Error analysis of phase detector based on Clarke transform and arctangent function in polluted grids - Carugati, Ignacio (2015)
Abstract Extracting phase information from a three-phase disturbed signal is a recurrent topic in power systems. The phase detector based on the Clarke transform and the arctangent function is a widely used technique to this end. However, the nonlinear nature of this method can derive in an error increment in the estimated phase angle when the input signal is distorted. These errors take the form of oscillating and constant terms and are not generally analyzed in the literature. Therefore, this work presents an error analysis of this phase detector that assesses its causes and effects. To do so, the disturbances over the estimated phase are modeled, the reduction of the phase detector performance is described, and the adverse effects produced by the absence of the pre-filter stage are discussed.